Pemberdayaan dan Pemasaran Produk UMKM Berupa Keripik Daun Singkong Melalui Bazar pada Festival Taneyan Lanjhang - Nurul Laily Syahada; Conny Dian Sumadi; Ilham Handika (BEKTI : Jurnal Pengabdian kepada Masyarakat, 2024)
Buddagan Hamlet 1 Larangan Luar Village has several potential villages developing within it. Village potential that is still developing includes the agricultural and livestock sectors. In the livestock sector, there are usually chicken and cattle farming centers. Meanwhile, in the agricultural sector, the superior commodities owned by Buddagan 1 Outer Ban Village include corn, tobacco, peanuts, chilies and cassava. The outsider community empowers each other's potential with various foods that have economic value. One type of potency that is often used is Samiler chips, the main ingredient of which is cassava. The many uses of cassava are often needed, but what is unique is that the cassava leaves are often not used and are used as feed for residents' cows. In line with the title of the KKN-T service in Larangan Luar Village, namely, optimizing economically valuable foods through cassava leaf chips. Apart from that, through the KKN-T work program the focus is on products that will be made into superior MSME products in Larangan Luar Village. In line with the UTM KKN-T students, they are optimizing cassava leaves into a food that has economic value and can be included in bazaar activities at the Taneyan Lanjhang Festival, Buddagan Hamlet 1, Larangan Luar Village.